Natural Hybridization between Populus Suaveolens Fisch. and populus Ciliata Wall. Ex Royale - Dhiman, R. C.; Gandhi, J. N.; Pande, P. K. (Indian Forester, 2014)
Paper presents morphological characterization of 64 half-sib progeny seedlings raised from seed collected from a single female Populus suaveolens Fisch. tree growing in the vicinity of P. ciliata and two saplings one each of P. ciliata and P. suaveolens raised from stem cuttings. K-Means clustering of leaf and branch morphological traits of progeny seedlings resulted in forming two clusters each of them represented with a sapling each of P. ciliata and P. suaveolens. The 95.45% individual seedlings (62 in number) were clustered with P. suaveolens (female parent) and 4.55% (2 in number) with P. ciliata (male parent). Some traits like, number of glands at the base of leaf blade, pubescence on the lower surface of leaf blade and leaf tip in progeny seedlings were associated with male parent- P. ciliata and two progeny seedlings with these traits got clustered with this species, whereas, the remaining progeny seedlings had leaf and stem traits similar to female parent- P. suaveolens.